Pengaruh Penerapan Model Discovery Learning Terhadap Keterampilan Berpikir Kritis Siswa pada Pelajaran IPAS - Soyhah, Elsa; Hanafi, Hanafi; Farhurohman, Oman (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2025)
The purpose of this study was to determine the effect of the discovery learning model on students' critical thinking skills in the IPAS (Science and Social Studies) subject, specifically on the topic of the States of Matter and Its Changes.The research method employed was a Quasi-Experimental design using the Non-equivalent Control Group Design. The study was conducted in the 4th grade of Madrasah Ibtidaiyah Islamiyah Ciwaru, where students were divided into an experimental group (receiving the discovery learning treatment) and a control group. The object of this research was the students' critical thinking skills. Data collection techniques included essay tests in the form of pretest and posttest, as well as observation. Data analysis was performed quantitatively using the t-test to determine the significance of the difference in the mean scores of the pretest and posttest between the two groups. The results showed a significant increase in critical thinking skills in the experimental class. The mean posttest score for the experimental class (86.63) was substantially higher compared to the control class (63.27). Based on the t-test analysis, the difference in the pretest and posttest scores between the two groups was significant, with a significance value (2-tailed) of 0.000 (p 0.05). The conclusion of this study is that the implementation of the discovery learning model is effective and can improve the critical thinking skills of 4th-grade students on the topic of the States of Matter and Its Changes.